Global Behaviors of a Chemostat Model with Delayed Nutrient Recycling and Periodically Pulsed Input - Kai Wang; Zhidong Teng; Fengqin Zhang (Discrete Dynamics in Nature and Society)
The dynamic behaviors in a chemostat model with delayed nutrient recycling and periodically pulsed input are studied. By introducing new analysis technique, the sufficient and necessary conditions on the permanence and extinction of the microorganisms are obtained. Furthermore, by using the Liapunov function method, the sufficient condition on the global attractivity of the model is established. Finally, an example is given to demonstrate the effectiveness of the results in this paper.